Detoxification of dihydroxypyridine by the rumen bacterium Synergistes jonesii - Domínguez Bello, M. G.; Rincón, M. T.; Lovera, M. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2011)
There are rumen bacteria capable of degrading toxic dihydroxypyridine compounds derived from mimosine, a non-protein amino acid found in Leucaena leucocephala. The degrading activity can be lost reversibly or irreversibly. In our study we determined the extension of bacterial growth and the degradation of 2,3 DPH under different conditions. The degradation of 2,3 DPH began once the late exponential phase of cultivation has been reached, and ended in 3 days. If additional 2,3 DHP is added to the degraded solution (once the original 2,3 DHP had been degraded) , the total degradation occured in 12 h. This activity was observed in saline solutions with pyruvate, in rumen fluids and argenine, but not in solutions supplemented with AGV or vitamins. Under strict anaerobic conditions growth and degradation were optimum. Airation of the samples diminished both growth and specific degradation activity. The maintenance of cultures without 2,3 DHP brought about loss of the degradation activity, which was recovered in some cases in re-cultivation in mediums with 2,3 DHP content, and a long lag phase (4 weeks) in the degradation activity (even when growth was normal). The presence of plasmides could not be confirmed. These results are relevant when manipulating laboratory degradation cultures. The degradation activity is present in extracts free of cells in two systems: An atmosphere of N2 and pyruvate (10mM) or an atmosphere of H2 and methyl viologen (0,5 mM). The products of’ the degradation process with 2,3 DHP are still unknown.